Gender and age features of dyslipidemia in the population of the Nizhny Novgorod region - N. Yu. Borovkova; V. K. Kurashin; A. S. Tokareva; T. E. Bakka; N. K. Pershina; E. S. Timoshchenko; A. A. Nekrasov; E. A. Ovchinnikova; N. N. Savickaya; M. A. Mironov; Yu. A. Balanova; A. E. Imaeva; et al. (Столичная издательская компания, 2023)
Aim. To study the gender and age characteristics of dyslipidemia in the population of the Nizhny Novgorod region.Material and methods. A total of 2501 people aged 35-74 among the population of the Nizhny Novgorod region were examined, selected by stratified multi-stage random sampling. The study was performed as part of the third epidemiological study ESSE-RF3. All respondents underwent an anthropometric survey, a questionnaire to identify chronic non-communicable diseases and related risk factors. The following laboratory tests were performed: total cholesterol (TC), low-density lipoproteins (LDL-C), high-density lipoproteins (HDL-C), triglycerides (TG). Among the entire cohort of patients at the time of blood sampling, 276 people (11,0%) were receiving lipid-lowering drugs. They were excluded from further analysis. Hypercholesterolemia (HCL) was recorded with a total cholesterol ≥5,0 mmol/l, an increased level of LDL-C - with a level ≥3,0 mmol/l, hypertriglyceridemia (HTG) - with a TG ≥1,7 mmol/l, a reduced level of HDL-C - with a level in males ≤1,0 mmol/l, in women ≤1,2 mmol/l.Results. The prevalence of HCL was 65,1%. In the young cohort (40-44 years), men were significantly more likely to have hypercholesterolemia, but in the middle (50-54 years) and older (60 years or more) age groups, this lipid metabolism disorder was observed with greater frequency among females. In addition, 68,9% of the respondents had elevated LDL-C levels. When studying the prevalence of this type of dyslipidemia in different age groups among men and women, a similar trend can be noted with similar TC values, but significant gender differences in the prevalence of elevated LDL-C levels l were revealed only in the 60-64 and 65-69 years groups. The prevalence of HTG among the adult population of the Nizhny Novgorod region was 42,6%. Among the 35-49 years and 55-59 years age groups, the prevalence of elevated TG levels was significantly more common among men. The incidence of decreased HDL-C levels was 13,3%. This type of dyslipidemia was significantly more often detected among men only in the youngest subgroup (35-39 years).Conclusion. Among the population of the Nizhny Novgorod region, hypercholesterolemia occurred in 65,1% of respondents, an increased level of LDL-C - in 68,9%, a HTG - in 42,6%, a reduced level of HDL-C - in 13,3%. The data obtained determine a high cardiovascular risk and require the development of prevention and treatment measures for lipid metabolism disorders.